Chronic Hypoxia-Induced Microvessel Proliferation and Basal Membrane Degradation in the Bone Marrow of Rats Regulated through the IL-6/JAK2/STAT3/MMP-9 Pathway. (25th January 2020) - Zhu, Mingming; Yang, Min; Yang, Quanyu; Liu, Wenling; Geng, Hui; Pan, Li; Wang, Lu; Ge, Rili; Ji, Linhua; Cui, Sen; Li, Zhanquan
Abstract : Chronic hypoxia (CH) is characterized by long-term hypoxia that is associated with microvessel proliferation and basal membrane (BM) degradation in tissues. The IL-6/JAK2/STAT3/MMP-9 pathway has been described in a variety of human cancers and plays an essential role in microvessel proliferation and BM degradation. Therefore, this study investigated the role of the IL-6/JAK2/STAT3/MMP-9 pathway in hypoxia-mediated microvessel proliferation and BM degradation in the rat bone marrow. Eighty pathogen-free Sprague Dawley male rats were randomly divided into four groups (20 per group)—control group, CH group (exposed to hypoxia in a hypobaric chamber at a simulated altitude of 5000 m for 28 d), CH + STAT3 inhibitor group (7.5 mg/kg/d), and CH + DMSO group. Microvessel density (MVD) and BM degradation in the bone marrow were determined by immunofluorescence staining and transmission electron microscopy. Serum IL-6 levels were assessed by enzyme-linked immunosorbent assay (ELISA), and the levels of P-JAK2, P-STAT3, and MMP-9 were assessed by western blot analysis and real-time reverse transcription PCR (RT-PCR). Hypoxia increased serum IL-6 levels, which in turn increased JAK2 and STAT3 phosphorylation, which subsequently upregulated MMP-9. Overexpression of MMP-9 significantly promoted the elevation of MVD and BM degradation. Inhibition of STAT3 using an inhibitor, SH-4-54, significantly downregulated MMP-9 expression and decreased MVD and BM degradation. Surprisingly, STAT3 inhibition also decreased serum IL-6 levels and JAK2 phosphorylation. Our results suggest that the IL-6/JAK2/STAT3/MMP-9 pathway might be related to CH-induced microvessel proliferation and BM degradation in the bone marrow.